Pain management during childbirth: A focus on non-pharmacological measures (Research, Society and Development, 2021)
Childbirth is considered a complex event, capable of being positively striking in the emotional sphere of the pregnant woman or even painful and traumatic. Offering good practices to women is necessary and means providing safe and quality support, taking into account physical and emotional comfort, respecting and helping in the way she wishes to give birth and, above all, offering her techniques capable of relieving her pain. This study aimed to evaluate the effectiveness of non-pharmacological methods for pain relief during childbirth and it was an observational descriptive study of the case series type. The research participants were parturients admitted to the Dr. João Bandeira Monte Maternity Hospital and who met some criteria, namely: parturients with an age range from 18 years old, of low risk, who were in the active phase of labor, with maximum of 6 centimeters of dilation of the uterine cervix and who agreed to receive non-pharmacological methods, in addition to accepting to participate in the research under the understanding and signing the Free and Informed Consent Form. Combined and isolated non-pharmacological methods were used to relieve the pain of parturients and the Visual Analogue Scale was applied to evaluate the effectiveness of these methods. For the analysis of this data, tables and graphs were used for statistical treatment with averages and percentages in Microsoft Office Excel 2016. The result of this study could demonstrate that there is effectiveness among the methods that were used within the context of the parturients who were attended, however, determinant requirements so that these can work individually in each woman. Subjectivity, choices, the parturient's previous knowledge about these methods, patient-professional interaction, among other aspects, must be taken into account.